2018
DOI: 10.1002/jez.2189
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of artificial light at night on sleep: A review and prospectus

Abstract: Natural cycles of light and darkness govern the timing of most aspects of animal behavior and physiology. Artificial light at night (ALAN)-a recent and pervasive form of pollution-can mask natural photoperiodic cues and interfere with biological rhythms. One such rhythm vulnerable to perturbation is the sleep-wake cycle. ALAN may greatly influence sleep in humans and wildlife, particularly in animals that sleep predominantly at night. There has been some recent evidence for impacts of ALAN on sleep, but critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 151 publications
0
50
1
Order By: Relevance
“…Moreover, the special issue also includes a timely perspective from ulsebrook, Jones, Mulder, and Lesku (2018) on the impacts of ALAN on sleep. Although evidence is accumulating for light pollution to alter sleep behavior, and nocturnal rest, the physiological basis for such changes is unknown.…”
Section: The Effects Of Alan At Different Levels Of Biological Orgamentioning
confidence: 99%
“…Moreover, the special issue also includes a timely perspective from ulsebrook, Jones, Mulder, and Lesku (2018) on the impacts of ALAN on sleep. Although evidence is accumulating for light pollution to alter sleep behavior, and nocturnal rest, the physiological basis for such changes is unknown.…”
Section: The Effects Of Alan At Different Levels Of Biological Orgamentioning
confidence: 99%
“…ALAN can decrease melatonin production at night [20], increase blood inflammatory markers [21] and increase susceptibility to pathogens [22]. However, the increase in nocturnal activity due to ALAN could have a major impact also on energy consumption and sleep [16,17]. Energy is a crucial and limited resource for animals, and there is a trade-off between investment decisions on behavioural and/or physiological processes and these trade-offs are often associated with fitness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies with great tits show that they are able to memorise locations of cached food by observing other bird species and steal resources, indicating the importance of cognition on fitness [26]. In birds, cognition is affected by sleep, and thus cognitive abilities may be altered by sleep disruption due to ALAN [16]. In a recent study, birds kept under constant daylight showed a disruption in their activity patterns and a deterioration in their cognitive performance [27].…”
Section: Introductionmentioning
confidence: 99%
“…We predicted that ALAN would compromise immune function, as previously demonstrated under constant bright light (Durrant et al ., ; Jones et al ., ). Given recent studies highlighting that even dim ALAN (<5 lx) is capable of affecting other physiological processes including circadian rhythm (Evans et al ., ; Brüning et al ., ), melatonin release (Dominoni et al ., ), sleep (Aulsebrook et al ., ), the timing of foraging and reproduction (Robert et al ., ; Russ et al ., ), physiological condition (Raap et al ., ), survival (McLay et al ., ), and immune function in vertebrates (Aubrecht et al ., ), we also predict that these effects on immune function would be observed at even the lowest levels of ALAN (namely, 1 lx).…”
Section: Introductionmentioning
confidence: 99%